Weaving educational and cultural values through traditional games at the Nglarak Blarak Festival - Dewantara, Yudhiet Fajar; Susanto, Prayogo; Hani, Hani (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
The Nglarak Blarak Cultural Festival held in Kulon Progo Yogyakarta serves as a strong response to issues faced in safeguarding the traditional games and culture amid the threats posed by globalization. This research seeks to understand how Nglarak Blarak Cultural Festival upholds and passes on local cultural practices, thereby arguing for the role of traditional games in the broader context of culture, education and socialization processes. A cultural ethnography approach was used, involving participatory observation during the 2023 festival, in-depth interviews with 28 participants (organizers, teachers, parents, and children), and documentary analysis of promotional materials and activity reports. One-on-one interactions with the festival organizers, participants as well as local community members aimed at comprehending what such games mean and their significance in the context of the culture. Such findings indicate that traditional games like egrang, dingklik ogek, and gerobak sodor are not only for fun but serve several other purposes, including the development of child’s multiple intelligence, social relations and culture through play. It also allows children to bond with their parents, so this is a method of culture in practice and children learn how to cooperate, play fair, and have discipline. Given the popularity of global culture, mass media and technological products, the festival offers an innovative way of cultural promotion aimed at appealing to young generations. The research concludes that these types of cultural festivals are important tools for retention of regional customs, strengthening of community spirit, and protection of cultural heritage in the fast changing social environment.